Formulation of the Divine Attachment Model as a Foundation for Tawhid Based Character Education: A Literature Analysis of the Hadith “Ihfazhillaha Yahfazka” - Anugrah Gustiranda; Benny Prasetya (Education Reserach Center, 2026)
This study aims to formulate a Divine Attachment model as a foundation for tawhid-based character education through a literature analysis of the Prophet’s hadith, “Ihfazhillaha yahfazhka” Guard Allah, and Allah will guard you. This research employs a qualitative approach using a systematic literature review method of scholarly articles published discussing character education, attachment theory, the psychology of religiosity, and the internalization of tawhid in Islamic education. The findings indicate that the hadith contains theological psychological principles concerning the affective and cognitive relationship between human beings and Allah, which cultivate God consciousness as the foundation of character. The Divine Attachment model is formulated through three primary dimensionsn the dimension of tawhid awareness, the dimension of transcendental emotional attachment and the dimension of behavioral. This model integrates Bowlby’s attachment theory with the Islamic concepts of, tawakkal, and taqwa. The implications of this study emphasize that tawhid based character education cannot merely take the form of transmitting normative values; rather, it must construct a secure attachment secure divine attachment that nurtures moral integrity, psychological resilience, and consistency in moral conduct.